The role of skill acquisition specialists in talent development - Pinder, R. A.; Maloney, M.; Renshaw, I.; Barris, S. (Talent identification and development in sport. International perspectives, 2021)
The overall aim of this chapter is to provide insights into the roles and impacts of Skill Acquisition (SA) specialists embedded across the talent identification and development pathway in Australia. To do this, we will overview the roles and skills of the SA specialist, and provide multiple 'applied insights' across Paralympic, Olympic and professional sports pathways. The chapter provides coaches, current and future SA specialists, as well as National Sporting Organisations (NSOs) with some (albeit snapshot) examples of the value and impact an SA specialist can have on the development and refinement of their programs. We highlight areas of research for specific stages of the pathway and provide a series of applied insights by providing short research summaries (e.g. an overview of current understandings on testing design) with recommended readings for you to explore in more depth. However, we focus largely on the roles of the SA specialist and practical implications and opportunities for development.